2017
DOI: 10.1007/s00204-017-2008-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple drug transporters mediate the placental transport of sulpiride

Abstract: Sulpiride is a typical antipsychotic drug for the treatment of schizophrenia, depression and other psychological disorders. It has been proven that a small amount of sulpiride could cross the human placenta using an ex vivo placental perfusion model. However, the placental transfer mechanism has not been elucidated. Considering the structure of sulpiride, we speculated that the transporters expressed in placenta might be involved in sulpiride uptake across the blood-placenta barrier. The aim of our study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 44 publications
2
9
0
1
Order By: Relevance
“…Our study clearly demonstrated that sulpiride was a substrate of hOCTN1 (K m of 249.5 ± 36 μ m ) and hOCTN2 (K m of 234.7 ± 35 μ m ) using MDCK cells stably expressing hOCTN1 or hOCTN2 (Figures and ; Table ), which was in accordance with our previous study (Bai et al, ). However, a previous study reported that sulpiride was not a substrate of hOCTN1 or hOCTN2 in transiently transfected cells (Dos Santos Pereira et al, ), which might be attributed to the alteration or loss of the function of hOCTNs in their applied cells during the experiment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study clearly demonstrated that sulpiride was a substrate of hOCTN1 (K m of 249.5 ± 36 μ m ) and hOCTN2 (K m of 234.7 ± 35 μ m ) using MDCK cells stably expressing hOCTN1 or hOCTN2 (Figures and ; Table ), which was in accordance with our previous study (Bai et al, ). However, a previous study reported that sulpiride was not a substrate of hOCTN1 or hOCTN2 in transiently transfected cells (Dos Santos Pereira et al, ), which might be attributed to the alteration or loss of the function of hOCTNs in their applied cells during the experiment.…”
Section: Discussionsupporting
confidence: 93%
“…(a) MDCK-hOCTN1/2 and mock cells were incubated in UpB (pH 6.4) with sulpiride (10-500 μM, 10 min); (b) MDCK-hOCT2 and mock cells were incubated in HBSS with sulpiride (5-500 μM, 10 min); (c) MDCK-hMATE1 and mock cells were incubated in AUB with sulpiride (1-100 μM, 2 min); (d) MDCK-hMATE2-K and mock cells in AUB with sulpiride (0.5-50 μM, 2 min) at 37°C. Data are expressed as mean ± SD, n = 3 Table 1), which was in accordance with our previous study (Bai et al, 2017). However, a previous study reported that sulpiride was not a substrate of hOCTN1 or hOCTN2 in transiently transfected cells (Dos Santos Pereira et al, 2014), which might be attributed to the alteration or loss of the function of hOCTNs in their applied cells during the experiment.…”
Section: Sulpiride Accumulation In Isolated Mouse Primary Renal Tubsupporting
confidence: 89%
“…MDCK-hOCTN2 cells were seeded into 24-well plates at a density of 2 Â 10 5 /well. On day 3 after seeding, cellular accumulation experiments were performed with the method described by our laboratory (Bai et al, 2017;Ma et al, 2017). Cells were washed twice and preincubated with Krebs-Ringer-Henseleit buffer for 10 minutes at 37°C, then 200 ml of Krebs-Ringer-Henseleit buffer containing The Mechanism of Maternal Plasma L-Carnitine Reduction d 3 -L-Car with or without pregnancy-related hormones (E2, P4, CORT, and cortisol) was added to initiate accumulation for 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…However, during the isolation and cultivation of PHTCs, the expression levels of transporters might be decreased or even lost, and PHTCs cannot proliferate and cannot form tightly connected monolayers. Besides, our previous study showed that mRNA expression levels of OCTN1/2, OCT3, and OAT4 are different between BeWo cells and PHTCs (47). Since cell models have their own limitations, to obtain more reliable results, transporter-transfected cell models, choriocarcinoma cell lines, and PHTCs were together applied in our study to better clarify placenta transfer of FTC.…”
Section: Discussionmentioning
confidence: 99%
“…MDCK-hOCT3, MDCK-hOCTN1/2, LLC-PK1-hBCRP, MDCK-hMDR1, MDCK-hMRP1/2/3, and the respective mock cells were seeded in 24-well plates at 2 ϫ 10 5 /well. Accumulation studies were carried out on day 3 according to a method created by our research team (47)(48)(49)(50). The activity of the transgenic cells mentioned above was tested by using classical substrates: MPP ϩ (10 M) for hOCT3, L-ergothioneine (3 M) for hOCTN1, d 3 -L-Car (3 M) for hOCTN2, Hoechst 33342 (10 M) for hBCRP, rhodamine 123 (5 M) for hMDR1, calcein-AM (10 M) for hMRP1/2, and CDCFDA (15 M) for hMRP3.…”
Section: Figmentioning
confidence: 99%